The effect of driven exercise on treatment outcomes for adolescents with anorexia and bulimia nervosa. Issue 4 (11th April 2014) - Stiles‐Shields, Colleen; DclinPsy, Bryony Bamford; Lock, James; Le Grange, Daniel
ABSTRACT Objective This study investigated the prevalence of driven exercise (DE) and its role in treatment outcome for adolescents with bulimia nervosa (BN) and anorexia nervosa (AN). Method Participants were 201 adolescents with an eating disorder (ED) (80 with BN and 121 with AN) presenting for outpatient treatment at two specialist clinics. All adolescents participated in one of two randomized controlled trials. Descriptive statistics were conducted to evaluate the presence and frequency of baseline DE. Exploratory hierarchical regressions were used to evaluate the effect of baseline DE on treatment outcomes. Results About 66.3% of adolescents with BN and 23.1% of adolescents with AN presented with baseline DE. The presence of baseline DE predicted significantly worse outcomes for adolescents with AN in terms of ED symptom severity (ps < .004); however, baseline DE did not significantly predict any of the evaluated outcomes for adolescents with BN (ps < .05). Discussion The results of this secondary exploratory data suggest that DE is prevalent for adolescents with BN and AN. However, DE may be related to different constructs for adolescents with AN than those with BN, suggesting differences in treatment needs. © 2014 Wiley Periodicals, Inc. (Int J Eat Disord 2015; 48:392–396)